2010
DOI: 10.4103/0974-8237.77678
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial glioblastoma multiforme with spinal metastases

Abstract: Glioblastoma multiforme is the most common malignant brain tumor in adults. Metastasis of intracranial glioblastoma via the cerebrospinal fluid to the spine is a rare occurrence. We present two cases of glioblastoma multiforme with spinal leptomeningeal spread who presented with back pain and paraparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Other authors suggest that ependymal invasion, fissuring of the ependyma due to hydrocephalus, and fragmentation of the tumor in contact with CSF are also risk factors for CSF dissemination [22]. In both patients with spinal metastases reported by Shah et al [23], primary GBM were in close proximity to the ventricles and there was ependymal enhancement in 1 patient. During surgery, the ventricles had also been opened inadvertently in both patients and this could eventually have explained the rapid dissemination to the spine according to the authors.…”
Section: Discussionmentioning
confidence: 96%
“…Other authors suggest that ependymal invasion, fissuring of the ependyma due to hydrocephalus, and fragmentation of the tumor in contact with CSF are also risk factors for CSF dissemination [22]. In both patients with spinal metastases reported by Shah et al [23], primary GBM were in close proximity to the ventricles and there was ependymal enhancement in 1 patient. During surgery, the ventricles had also been opened inadvertently in both patients and this could eventually have explained the rapid dissemination to the spine according to the authors.…”
Section: Discussionmentioning
confidence: 96%
“… 5 First reported in 1931, 3 CSF dissemination of GBM occurs in approximately 15% to 25% of GBM patients, although the accurate incidence reported in different studies ranged a lot. 6 For infratentorial GBM, the incidence was higher. Witoonpanich once reviewed 600 GBM patients in a retrospective study, and found that symptomatic CSF dissemination just occurred in 2% of them.…”
Section: Discussionmentioning
confidence: 98%
“…Surgery may be attempted if there is a symptomatic, large metastatic deposit causing cord compression as in our case, but usually leptomeningeal metastases are not amenable to surgery due to the diffuse nature of the disease. [ 11 ] The treatment modality for these patients is mainly palliative. RT is the most commonly used treatment modality, with a total dose of 25–40 Gy.…”
Section: Discussionmentioning
confidence: 99%